Analisis Proses Pemesinan dan Biaya Manufaktur Pembangkit Listrik Tenaga Hidro Mini (PLTHM) - Yudhi Chandra Dwiaji; Nurato; Muh. Anhar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2017)
Indonesia had once become the fuel exporter, it now becomes the fuel importer. To overcome this crisis, then the best option is to increase the utilization of the alternative energy, like what has been conducted in other countries; both developed and developing countries. Renewable energy is a non-fossil energy derived from nature which is designed and cared in such way, it will not be discharged because the amount is unlimited, for example: solar panels, biomass, bioethanol, water energy, heat energy, nuclear energy, tidal energy, wave energy and others. The aim of this research are: 1) to determine the stages in manufacturing process of mini hydro from the early machining process until the final process of quality control, 2) to determine the calculation of the time and costs in the manufacturing process of mini hydro in details. From the analysis of the cost and the manufacturing process of mini hydro, where the generator produces electric energy maximum of 1 KW, driven by a waterwheel that uses frame brackets 50 x 50 x 5 mm, the total cost of making the mini hydro is IDR 6.423.900, it is obtained from the sum of the costs which have been calculated, such as manufacturing cost IDR 5.444.000, design cost IDR 544.400 and unexpected cost IDR 435.500. The required total time in the manufacturing process of mini hydro is 14 hours. The use of micro-hydro energy can be used as an alternative renewable energy to overcome the problems of large power consumption and the provision of electrical energy that is not evenly distributed, especially in rural areas. The use of this micro-hydro is in accordance with the environmental conditions in Indonesia which has a lot of hills and rivers.